Fishery and biological aspects of Euphausia superba on its fishery grounds at the South Shetland Islands and in the Bransfield Strait in March-May, 2006 - Zhuk, N. N. (Ukrainian Antarctic Journal, 2012)
Analysis of fishery operations of the Ukrainian fishing vessel “Кonstruktor Koshkin” at the Antarctic krill Euphausia superba fishery was given. Reasons of formation and disintegration of its fishery aggregations were considered. Characteristics of krill age-mass composition and biological state were given, as well as spatial distribution features of its different size groups on the fishery grounds at the South Shetland Islands and in the Bransfield Strait (statistical subarea FAO 48.1) in the autumn season, 2006.